Role of the S layer in morphogenesis and cell division of the archaebacterium Methanocorpusculum sinense. - Pum, D (1991)
Thin sections, freeze-etched, and negatively stained preparations of Methanocorpusculum sinense cells reveal a highly lobed cell structure with a hexagonally arranged surface layer (S layer). Digital image processing of negatively stained envelope fragments show that the S layer forms a porous but strongly interconnected network. Since the S layer is the exclusive cell envelope component outside the cytoplasmic membrane it must have a cell shape determining and maintaining function. Although lattice faults such as disclinations and dislocations are a geometrical necessity on the surface of a closed protein crystal, our data indicate that they also play important roles as sites for the incorporation of new morphological units, in the formation of the lobed cell structure, and in the cell division process. In freeze-etched preparations of intact cells numerous positive and negative 60 degree wedge disclinations can be detected which form pentagons and heptagons in the hexagonal array. Complementary pairs of pentagons and heptagons are the termination points of edge dislocations. They can be expected to function both as sites for incorporation of new morphological units into the lattice and as initiation points for the cell division process. The latter is determined by the ratio between the increase of protoplast volume and the increase in actual S-layer surface area during cell growth. We postulate that this mode of cell fission represents a common feature in lobed archaebacteria which possess an S layer as the exclusive wall component.